Interwoven Nitinol Stents versus Drug Eluting Stents in the Femoro-Popliteal Segment: A Propensity Matched Analysis. (November 2019) - Saratzis, Athanasios; Rudarakanchana, Nung; Patel, Sanjay; Diamantopoulos, Athanasios; Lea, Talia; Corbo, Ben; Gradinariu, George; Katsanos, Konstantinos; Zayed, Hany; ,
Abstract : Background: Percutaneous transluminal angioplasty (PTA) is a common procedure in patients with peripheral arterial disease (PAD) affecting the femoropopliteal segment (F-P). Biomimetic nitinol stents (Supera peripheral stent, SPS) and drug eluting stents (DES) were designed to improve the longevity of F-P PTA; however, their performance has not been compared in a pragmatic setting, taking atherosclerotic plaque characteristics into account. Methods: Overall, 296 consecutive patients (mean age: 73 y, SD: 11 y, 65% male, 68% with chronic limb threatening ischaemia) who underwent F-P PTA using SPS or DES between 2013 and 2018 were identified from a prospectively maintained institutional database. Patient and plaque characteristics, including F-P plaque characterisation based on computed tomography, were collected; 121 case matched pairs were created using a propensity score based on patient and plaque data. Results: During the median two year follow up, 28% of the cohort (32% SPS vs. 24% DES, p = .07) developed target lesion restenosis (TLR) > 50%. Among the 121 case matched pairs of patients, those with SPS vs. DES were not significantly more likely to develop TLR >50% (31% vs. 27%, p = .34), or stent occlusion (13% vs. 12%, p = .85 – secondary patency rate 87% vs. 88%), have a major amputation (10% vs. 6%, p = .16), require re-intervention (14% vs. 9%, p = .12), or die (7% vs. 4%, p = .31). Plaque calcification did not predict restenosis or occlusion in either stent group, both in the matched and non matched populations. Multivariable analysis adjusted for patient and plaque characteristics revealed that the main predictors of restenosis >50% at two years were female sex [odds ratio (OR): 2.05, p = .01], hypertension (OR: 2.10, p = .04) and previous F-P occlusion (OR: 1.35, p = .04). Conclusion: Medium term results following F-P PTA with either SPS or DES are comparable, regardless of plaque calcification and patient characteristics.